PERAN KELUARGA DALAM KUALITAS ANAK USIA DINI MENURUT PANDANGAN TAFSIR TARBAWI - Rasyid Tahta Rasyid Tahta Nugraha; Sayla Ar Rahmah Hafiidzah; Kayza Safitri Nasution; Shila Dara Aulia (Hikmah: Journal of Islamic Studies, 2023)
AbstractThe family is the main pillar for children's education, the attitude of parents must also support the development of children's potential. The role of the family is very important in determining the quality of early childhood education. This study aims to determine the role of the family in the quality of early childhood in the view of tarbawi interpretation. This study used a qualitative method using a literature study approach (library research). The results of this study indicate that the attention given by parents to early childhood education is very important in helping children build a strong foundation, develop their potential, and help them achieve success in the future. The role of the family is very dominant in the quality of a child, for example. Parents provide emotional and physical support to their children, and encourage them to explore and learn through play. Tarbawi's interpretation of Surah Luqman verses 12-14 emphasizes the importance of character education in early childhood through teaching moral and religious values, and places an emphasis on the role of the family in fostering and educating their children to become a strong and empowered generation.AbstrakArtikel ini bertujuan untuk memperkuat wacana pendidikan mengenai kontra radikalisasi dan intoleransi yang menjadi ancaman dunia pendidikan saat ini. Fenomena ini memerlukan upaya yang sistematis untuk menanamkan nilai-nilai moderasi beragama atau Islam wasathiyah melalui pendidikan. Dengan menggunakan pendekatan analisis wacana kritis, penelitian ini mengeksplorasi lebih jauh bagaimana ide-ide fundamentalisme, radikal, dan intoleransi dapat dilawan melalui landasan Islam wasathiyah dan pendidikan kontra-radikal dalam lingkungan pendidikan. Temuan dalam penelitian ini menunjukkan bahwa nilai-nilai wasatiyah Islam seperti moderasi (tawassuth), toleransi (tasamuh) dan persaudaraan (ukhuwah) perlu diterapkan dalam pendidikan dan dimasukkan dalam kurikulum pendidikan dalam hubungannya dengan berbagai mata pelajaran.